Numerical analysis of repaired wall loss defect pipelines for optimum composite wrap thickness (Fracture and Structural Integrity, 2022)
The paper presents the numerical analysis of failure pressure of wall loss defect metallic pipelines and validate it with experimental results. An optimization of composite thickness for repair of wall loss defect pipeline is also carried out using numerical analysis. A nonlinear explicit FE code with constitutive models for metallic steel and composite material to failure modelling was used. Three different cases: non-defective pipe, wall loss defective pipe and composite repaired of defective pipe are considered. It was found that the numerical results are in good agreement with the analytical results in all the three cases. The theoretical failure pressure determined by ISO/TS 24817 standard for wall loss defect pipe is highly conservative compared to the numerical failure pressure for the given composite repair thickness. Additionally, the numerical study on optimization of repair thickness revealed that lower composite repair thickness can also sustain the designed failure pressure (composite repair thickness of 8.4 mm can sustain the same designed pressure instead of 16.1 mm thickness), which implies there is scope to further reduce the composite thickness, which ultimately reduce the repair cost.
Keywords: Composite Repair; Numerical modelling; Optimisation; Composite thickness; Wall loss defect; Corroded pipeline